(untitled) (Quinto Sol, 2019)
The processes of incorporation of border areas to National State in formation during the second half of the 19th century constitute a particular field of analysis. In current approaches, the frontier is conceived as a space constituted by varied and complex relationships between groups in contact that include coexistence as well as conflicts, negotiations and agreements. From this perspective, in the present text we distinguish those actors who participated in the Santa Fe north border during the Argentine Confederation period. In turn, we provide a brief glimpse into the relations maintained to define certain aspects that also allow us to draw up later lines of inquiry: the military organization of the Santa Fe north boundary, provincial expeditions and advance project over Chaco territory and, finally, the weave of frontier relations held by indigenous peoples, countrymen and missionaries.